Igualdad jurídica y género - Martínez Muñoz, Juan Antonio (Anuario de Derechos Humanos. Nueva Época, 2009)
This paper discusses the way to resolve some hard problems in order to determinate the meaning of the legal equality and the repercussions that involves the genre ideology in it. Particularly it focuses on the different projections over the equality of the two confronted anthropological traditions and how the competitiveness of free political communities is the only solution.
Keywords: Legal equality; Genre; Law; Rights; Competitive